Epidural versus PCA Pain Management after Pectus Excavatum Repair: A Multi-Institutional Prospective Randomized Trial - Sujka, Joseph A.; Dekonenko, Charlene; Millspaugh, Daniel L.; Doyle, Nichole M.; Walker, Benjamin J.; Leys, Charles M.; Ostlie, Daniel J.; Aguayo, Pablo; Fraser, Jason D.; Alemayehu, Hanna; Peter, Shawn D. St. (European Journal of Pediatric Surgery, 2019)
Introduction Postoperative pain control remains the primary reason for inpatient stay after minimally invasive repair of pectus excavatum. In a previous study, our group reported that early pain control was better in patients managed with a thoracic epidural, while late pain control was better in patients managed with patient-controlled analgesia (PCA). After revising our epidural transition and modifying the PCA protocol, we conducted a multi-institutional prospective randomized trial to evaluate these two pain control strategies.Materials and Methods Patients were randomized to epidural or PCA following minimally invasive repair of pectus excavatum with standard protocols for each arm. Primary outcome was length of stay with secondary variables including mean patient pain scores, complications, and parental satisfaction. Scores were pooled for the two groups and reported as means with standard deviation. Results were compared using t-tests and one-way analysis of variance with p-value < 0.05 determining significance.Results Sixty-five patients were enrolled, 32 epidural and 33 PCA. Enrollment was stopped early when we developed an alternative strategy for controlling these patients' pain. There was no difference in length of stay in hours between the two arms; epidural 111.3 ± 18.5 versus PCA 111.4 ± 51.4, p = 0.98. Longer operative time was found in the epidural group. Nine patients in the epidural group (28%) required a PCA in addition to epidural for adequate pain control. Mean pain scores were lower on postoperative day 0 in the epidural group compared with the PCA groups, but were otherwise similar.Conclusion In our prospective randomized trial, PCA is just as effective as thoracic epidural in decreasing early postoperative pain scores after minimally invasive repair of pectus excavatum.
Keywords: PCA; epidural; pectus excavatum; postoperative pain control